Multi-objective topological reconfiguration of a Low Voltage electrical distribution network by optimal repositioning of MV / LV multi-transformers using Elitist Algorithms of the NSGA-II type - Oloulade, Arouna; MOUKENGUE IMANO, ADOLPHE; FIFATIN, François-Xavier; HOUNKPE HOUENOU, GERVAIS AMAVI; Gnansounou, D. Larios; Tanimonmon, Mahamoud; Deguenon, Mitterand; Aza –Gnandji, Maurel R; VIANOU, Antoine (My University, 2020)
Several transformers in the Low-Voltage (LV) distribution networks of Benin Electric Company are off-center from theloads’sgravity connected to them. This situation is due to the continuous growth of loads on these networks and the extension of LV lines. This paper presents an approach based on the elitist NSGA-II genetic algorithmfor optimalrelocation of MV/LV multi-transformers in a quasi-sinister distribution network. The results obtained show that the power losses which were 72.6 kW in the basic configuration are reduced for the case of single-transformer positioning by 51.07% and by 91.80% for the multi-transformer positioning of two 400kVA units. The evaluation of the profitability of the two options revealed that the optimal positioning of 400 kVA multitransformers in the Zogbadjè network is economically and technically viable compared to the first option of positioning an 800kVA transformer at node 8.This study also showed that the Return On Investment (ROI) is 5 month 15 days with a Net Present Value (NPV) equal to 315,770,000 CFA . This project of optimal relocation of distribution transformers is highly relevant and effective in reducing losses and operating costs of distribution networks.
Keywords: Position; optimal; distribution Transformers; radial network; NPV- NSGA-II